Time of Diapause Termination in the Pistachio Seed Wasp Eurytomα plotnikovi (Hymenoptera: Eurytomidae) ίη Northem Greece and Under Certain Photoperiods and Temperatures - Haralambidis, C. G.; Tzanakakis, M. E. (ENTOMOLOGIA HELLENICA, 2000)
Mummified pistachios containing fully grown diapause larvae of Eurytoma plotnikovi Nikol’skaya were collected from mid-November on from trees in coastal northern Greece and placed in a field cage. Every 5 weeks, fruits from the cage and from the trees were placed at 16L:8D h and 26°C. Pupation within I or 2 weeks showed that diapause was terminated between early April and early May. Two years later, strarting in early September, mummified fruits from the same trees were collected at bimonthly intervals and subjected fora few to several months to combinations of certain temperatures and photoperiods, followed by different conbinations of temperatures and photoperiods, then to 16L:8D h and 25°C. In larvae of early September, 6 months at 6°C was the most effective treatment for diapause termination. Diapause was also terminated or almost so after: (1) 4 months at 25°C and long photophase followed by 5 months at 14° or 6°C, (2) 4 months at 20°C and a 12 h photophase followed by 3 months at 14° or 6°C, (3) 4 months at WC and short photophase followed by 3 months at 6°C, and (4) 4 or 6 months at WC and short photophase. The results are in line with previous work, showing that, in larvae picked in early autumn, low temperatures and short days fora few to several months followed by high temperatures and a long day favor an early and synchronous termination of diapause. The time of diapause termination being in mid-spring, long days seem to be a reasonable signal for diapause termination, as shown by previous work. In larvae of early January, for a synchronous diapause termination four months at 20°C and a 12 h photophase followed by 3 months at WC and an 8 h photophase was the most effective treatment, without the need for a long-day final condition.